Dampak Pemanasan Global terhadap Fenologi Tanaman Kecipir (Psopocarpus tetragonolobus) dan Hubungannya dengan Serangga Pollinator - Yuni Rokhdita Rahayuningtyas; Eming Eming Sudiana; Elly Proklamasiningsih (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2020)
Global warming or often referred to as global warming is a form of imbalance of ecosystems on earth due to the process of increasing the average temperature of the atmosphere, sea, and land on earth. The impact of global warming can make agricultural plants flower faster while pollinating insects are not ready so that the reproductive cycle is disrupted. Studying temperature changes as a result of global warming on an organism can be represented by an altitude gradient. The study aims to determine the effect of temperature changes on the phenology of winged bean plants (Psophocarpus tetragonolobus) which is described by the gradient of altitude and to determine the diversity of pollinator insects. The independent variable in this study is the difference in the gradient in elevation of the place, while the dependent variable is the phenology of the development of winged bean flowers and pollinator insects. The results of the study of abiotic factors showed that air temperature and sunlight intensity decreased in line with the increase in altitude from the surface of the seawater, while the humidity increased. The phenological analysis of winged bean plants showed the influence of altitude on plant height, number of leaves and branches, time of the first appearance, number of flowers and flower size as well as the diversity of pollinator insects.